Kesulitan Membaca Al-Qur’an di TPQ/TPSQ Mushala Nurul Haq Kenegarian Sungai Dareh - Yoga Novyardi Yoga (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
In this era, reading the Quran is not a difficult thing to do, this is due to technological advances and so on. Reading the Quran can be done through a smartphone or through other technological sophistication. However, in the kenagarian sungai dareh, children are still taught manually, namely learning to recite at TPQ/TPSQ or mushalah. This is useful so that when learning to read the Quran children or students understand and understand better and are precise in the pronunciation of makhrajul letters. The method used in this study is to use survey research with qualitative descriptive techniques, where this study aims to produce data analysis through data collection instruments with observation techniques, interviews, and documentation. The results showed that there are still many students who have difficulty in reading the Quran, such as difficulties for young students who are just starting to learn to recite and not infrequently there are also students who have grown up who are still not taught in reading the Quran. this is due to the presence of internal factors and external factors. The role of parents is very much required in guiding their children in learning to recite not only at TPQ / TPSQ but at home it is also necessary to do so that their children can read the Quran more fluently and precisely in the pronunciation of makhrajul letters.